Lipid deposition patterns among different sizes of three commercial fish species. (6th December 2017) - Ren, Wei; Li, Jingqi; Tan, Peng; Cai, Zuonan; Mai, Kangsen; Xu, Wei; Zhang, Yanjiao; Nian, Rui; Macq, Benoit; Ai, Qinghui
Abstract: This study was conducted to compare lipid deposition pattern of three fish species among fish size, Large yellow croaker ( Larmichthys crocea ), Japanese seabass ( Lateolabrax japonicus ) and Turbot ( Scophthalmus maximus L.), Using magnetic resonance imaging technology for adult fish, results showed that lipid of large yellow croaker mainly deposits in abdominal cavity wall, while for Japanese seabass mainly deposit in visceral adipose tissue and for turbot lipid mainly distribute subcutaneous tissue. Three sizes for each species were selected: S1 (small size), S2 (intermediate size) and S3 (big size), to examine chemical analysis. Results of chemical analysis indicated that whole body lipid content of large yellow croaker significantly increased with the increase in body weight, but Japanese seabass and turbot significantly decreased ( p  < .05). Lipid content of muscle and intestinal tract in large yellow croaker significantly increased with the increase in body weight ( p  <   .05), but lipid content of adipose tissue, kidney, heart and skin in S2 group were higher than S1 and S3 groups ( p  <   .05). Lipid content of liver, eye, kidney and brain in Japanese seabass significantly increased with the increase in body weight ( p  <   .05), but lipid content of stomach and heart showed an opposite trend. Lipid content of liver, adipose tissue, skin and eye in turbot significantly decreased ( p  <   .05), but lipid content of brain significantly increased with the increase in body weight ( p  <   .05). The results indicated that lipid content of different tissues in fish presented different trends, which was species‐dependent.